2022
DOI: 10.1186/s13584-022-00543-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 pandemic on primary care physicians in Israel, with comparison to an international cohort: a cross-sectional study

Abstract: Background The COVID-19 pandemic had a major impact on primary care and primary care physicians (PCPs) in Israel and around the world. There is paucity of information regarding treatment of patients with COVID-19 in the community, since most research was performed in hospitals. The aim of this study was to describe the Israeli PCPs’ experience. Methods This study is a part of an international cross-sectional study, the PRICOV-19. A translated vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Some participants had opportunities to communicate directly with public health and system managers, which improved their personal experiences and instilled a sense that primary care providers were valued. Our findings are consistent with studies from other high-income countries that found that during the early stages of the pandemic, primary care providers had to manage rapidly evolving information and practice guidelines that focused on secondary settings (Gray and Sanders, 2020;Kurotschka et al, 2021;Smyrnakis et al, 2021;Sotomayor-Castillo et al, 2021;Adler et al, 2022;Mahlknecht et al, 2022;Van Poel et al, 2022;Makowski et al, 2023). We also identified attributes of information that FPs valued: credible, clear, consistent, collated, brief, actionable, bi-directional, and relevant to the primary care setting.…”
Section: Discussionsupporting
confidence: 88%
“…Some participants had opportunities to communicate directly with public health and system managers, which improved their personal experiences and instilled a sense that primary care providers were valued. Our findings are consistent with studies from other high-income countries that found that during the early stages of the pandemic, primary care providers had to manage rapidly evolving information and practice guidelines that focused on secondary settings (Gray and Sanders, 2020;Kurotschka et al, 2021;Smyrnakis et al, 2021;Sotomayor-Castillo et al, 2021;Adler et al, 2022;Mahlknecht et al, 2022;Van Poel et al, 2022;Makowski et al, 2023). We also identified attributes of information that FPs valued: credible, clear, consistent, collated, brief, actionable, bi-directional, and relevant to the primary care setting.…”
Section: Discussionsupporting
confidence: 88%
“…Maintaining access and continuity is particularly challenging during health crises. Disruptions to regular service delivery in primary care during the COVID-19 pandemic have been widely discussed in the literature [ 76 – 78 ] and are especially relevant for vulnerable patient groups such as patients with chronic diseases [ 47 , 79 ] or elderly patients [ 36 , 37 ]. Such disruptions were also reported by the interviewees of all investigated countries.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in video consultations was also found in the international PRICOV-19 cohort, where the indicated daily use of video consultations increased from 1.3 to 10.5 % [ 10 ]. It is possible that Norwegian GP practices more easily than many other countries could launch such services, as all Norwegian GPs already used electronic patient record systems with a mandatory connection to a high-security digital platform.…”
Section: Discussionmentioning
confidence: 98%